1995
DOI: 10.1084/jem.182.6.1825
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the balance of cytokine production and the signal transducer and activator of transcription (STAT) transcription factor activity by cytokines and inflammatory synovial fluids.

Abstract: SummaryThe balance between type 1 and 2 T helper cell cytokine production plays an important role in several animal models ofautoimmunity, and skewed patterns of cytokine expression have been described in human inflammatory diseases . Many cytokines activate signal transducer and activation of transcription (STAT) transcription factors, which, in turn, activate transcription ofinflammatory effector genes. We used mononuclear cell priming cultures and inflammatory synovial fluids (SFs) derived from arthritis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 23 publications
(22 reference statements)
5
31
1
1
Order By: Relevance
“…STAT proteins are critical in mediating intracellular effects of various cytokines and are implicated in the expression of many inflammatory effector genes. Active STAT-3 has been detected in cells from inflamed joints (30), and synovial fluids from rheumatoid arthritis patients can activate STAT-3 but not STAT-1 in monocytes (24). Similarly, we found that B. burgdorferi infection resulted in activation of STAT-3 and STAT-6, but not STAT-1.…”
Section: Discussionsupporting
confidence: 72%
“…STAT proteins are critical in mediating intracellular effects of various cytokines and are implicated in the expression of many inflammatory effector genes. Active STAT-3 has been detected in cells from inflamed joints (30), and synovial fluids from rheumatoid arthritis patients can activate STAT-3 but not STAT-1 in monocytes (24). Similarly, we found that B. burgdorferi infection resulted in activation of STAT-3 and STAT-6, but not STAT-1.…”
Section: Discussionsupporting
confidence: 72%
“…The first reports of JAK/STAT activation in RA described constitutive STAT-3 DNA binding activity in freshly isolated RA synovial fluid (SF) mononuclear cells, and showed that soluble factors contained in RA SFs effectively activated STAT-3 in control human monocytes (12,13). IL-6 was the major STAT-3-activating factor present in RA SFs.…”
Section: Stat Activation In Ra Synovitismentioning
confidence: 99%
“…Studies on activation of STATs in RA synovial fluid (SF) cells have yielded conflicting results. Activated STAT-3 has been found in SF cells from RA patients (5). Furthermore, SF from RA patients has been shown to induce STAT-3 activation in monocytes (6); this activity could be blocked by neutralization of IL-6.…”
mentioning
confidence: 99%